FIFA 2010 World Cup: Preparedness of Zimbabwean Hotels. - Zibanai Zhou (Publishing India Group., 2023)
Staging a mega sport event such as the world cup has been traditionally viewed as a golden opportunity for urban regeneration and economic development. Research into the preparedness of hospitality service providers to host millions of visitors associated with world cup sport events is limited. This paper discusses the state of preparedness for Zimbabwean hotels in anticipation of the world cup sport event hosted by South Africa. The study used a purposive sampling of twenty local hotel players in the category of 3-5 stars. Data were collected through self-administered eighteen questionnaires. Findings show that the majority of hotels have increased accommodation capacity ahead of the event. However, findings also demonstrated differences in the level of preparedness for local hotels with hotels in the northern region in the back foot than their southern counterparts. All operators were equally concerned about an ineffective air transport system. Service providers showed lack of confidence that they will benefit from the world cup event due to the poor national payment system and excessive hotel rates. These findings contradict planned refurbishments and human resource training that are currently underway. The study recommends urgent destination endorsement, re-introduction of credit cards, and consensus on the appropriate pricing strategy.